Anal human papillomavirus genotype distribution and its associations with abnormal anal cytology among men who have sex with men - I Ketut Agus Somia; Tuti Parwati Merati; Dewi Dian Sukmawati; Ni Wayan Winarti; IGAA Elis Indira; Ida Bagus Dwija Putra; Made Yogi Oktavian Prasetia (Universa Medicina, 2022)
BACKGROUND Anal human papillomavirus (HPV) is associated with the severity of anal cytologic abnormalities that are precancerous lesions. Knowledge of HPV type distribution in populations at risk for anal cancer is needed. This study investigated anal HPV infections and cytological abnormalities among men who have sex with men (MSM).